Risk of genetic maladaptation due to climate change in three major European tree species. (10th August 2017) - Frank, Aline; Howe, Glenn T.; Sperisen, Christoph; Brang, Peter; Clair, J. Bradley St.; Schmatz, Dirk R.; Heiri, Caroline
Abstract: Tree populations usually show adaptations to their local environments as a result of natural selection. As climates change, populations can become locally maladapted and decline in fitness. Evaluating the expected degree of genetic maladaptation due to climate change will allow forest managers to assess forest vulnerability, and develop strategies to preserve forest health and productivity. We studied potential genetic maladaptation to future climates in three major European tree species, Norway spruce ( Picea abies ), silver fir ( Abies alba ), and European beech ( Fagus sylvatica ). A common garden experiment was conducted to evaluate the quantitative genetic variation in growth and phenology of seedlings from 77 to 92 native populations of each species from across Switzerland. We used multivariate genecological models to associate population variation with past seed source climates, and to estimate relative risk of maladaptation to current and future climates based on key phenotypic traits and three regional climate projections within the A1B scenario. Current risks from climate change were similar to average risks from current seed transfer practices. For all three climate models, future risks increased in spruce and beech until the end of the century, but remained low in fir. Largest average risks associated with climate projections for the period 2061–2090 were found for spruce seedling height (0.64), and for beech bud break and leaf senescence (0.52 and 0.46). Future risks for spruce were high across Switzerland. However, areas of high risk were also found in drought‐prone regions for beech and in the southern Alps for fir. Genetic maladaptation to future climates is likely to become a problem for spruce and beech by the end of this century, but probably not for fir. Consequently, forest management strategies should be adjusted in the study area for spruce and beech to maintain productive and healthy forests in the future. Abstract : To guide forest management, we investigated potential genetic maladaptation to future climates in Norway spruce, silver fir, and European beech in Switzerland. Based on data from a genecological field test, we project all three species to be adapted to the near‐term climates of 2021 to 2050. Considering the climates of 2061 to 2090 (see figure), fir is projected to be still largely adapted (b), whereas spruce and beech are expected to be maladapted in many regions (a, c). Consequently, spruce and beech deserve greater attention when designing management strategies for maintaining healthy Swiss forests.